White light interferometer with color CCD for 3D-surface profiling of microsystems - Upputuri, Paul Kumar (2015)
White light interferometry (WLI) is a state-of-the-art technique for high resolution full-filed 3-D surface profiling of Microsystems. However, the WLI is rather slow, because the number of frames to be recorded and evaluated is large compared to the single wavelength phase shifting interferometry. In this paper, we combine white light interferometer with a single-chip color CCD camera which makes the measurement faster, simpler, and cost-effective. The red-bluegreen (RGB) color interferogram stored in a computer is then decomposed into its individual components and corresponding phase maps for red, green, and blue components are calculated independently. The usefulness of the technique is demonstrated on reflective micro-scale-samples.